2019
DOI: 10.3390/ijerph16050856
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Fluoride to the Pathogenesis of Eye Diseases: Molecular Mechanisms and Implications for Public Health

Abstract: This study provides diverse lines of evidence demonstrating that fluoride (F) exposure contributes to degenerative eye diseases by stimulating or inhibiting biological pathways associated with the pathogenesis of cataract, age-related macular degeneration and glaucoma. As elucidated in this study, F exerts this effect by inhibiting enolase, τ-crystallin, Hsp40, Na+, K+-ATPase, Nrf2, γ -GCS, HO-1 Bcl-2, FoxO1, SOD, PON-1 and glutathione activity, and upregulating NF-κB, IL-6, AGEs, HsP27 and Hsp70 expression. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 295 publications
(327 reference statements)
0
11
0
Order By: Relevance
“…Glaucoma is clinically defined as progressive damage to the optic nerve and visual field (VF) loss principally associated with a loss of retinal ganglion cells and is widely reported as a leading cause of irreversible visual impairment and blindness [1,2]. Increased intraocular pressure is a major risk factor for glaucoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is clinically defined as progressive damage to the optic nerve and visual field (VF) loss principally associated with a loss of retinal ganglion cells and is widely reported as a leading cause of irreversible visual impairment and blindness [1,2]. Increased intraocular pressure is a major risk factor for glaucoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have further suggested that inhibitors of NKA may also contribute to disorders associated with loss of NKA activity [18]. This hypothesis is supported by two current studies which infer a causal association between F − exposure and pathophysiological states associated with loss of NKA activity including iodine deficiency [110] and degenerative eye diseases [53]. Among the many molecular mechanisms identified in these latter studies was the contribution of F − to loss of NKA activity.…”
Section: Discussionmentioning
confidence: 57%
“…Past studies have also shown that reduced NKA activity may underlie the pathophysiological aspects linked to the prehypertensive status in humans [40,545]. Additionally, it has been widely documented that inhibition of NKA activity is associated with hypertension [44,45,46,47,48,49,50,51,52,53]. Again, several human studies have found that exposure to excessive F is closely associated with hypertension [546,547,548,549,550].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium containing H 2 and the blank medium were added into 96-well plates, respectively. The media were mixed with 10 μl cell counting kit 8 (CCK-8) solution (Dojindo, Japan) at different time points (2,4,6,12,24,36, and 48 hours) and incubated for 2 hours. The absorbance at 450 nm was determined by Imark enzyme labeling instrument (Bio-Rad).…”
Section: Cell Counting Kit-8 Test Of Cecsmentioning
confidence: 99%